Bilateral Ptosis as Initial Presentation of Gliomatosis Cerebri: Case Report - Kovanda, Timothy; Braca, John; Prabhu, Vikram (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Gliomatosis cerebri is a rare, diffuse glioma of neuroepithelial origin involving more than two cerebral lobes. Clinical presentation of gliomatosis cerebri is variable and depends on the degree, extent, and location of cortical involvement. Signs and symptoms related to supratentorial cortical involvement predominate and the diagnosis is reached through a combination of clinical, radiographic, and histopathological evaluations. This is a report of a young man who presented with visual problems and bilateral ptosis, which were eventually attributed to gliomatosis cerebri. Standard radiation and chemotherapy were administered but the patient eventually succumbed to the disease. The unique clinical presentation is discussed in light of this rare neoplasm of the central nervous system.
Keywords: gliomatosis cerebri; ptosis; radiation therapy; temozolomide